Degradation of feed for ruminant in a Consecutive Batch Culture (CBC) system - Ismartoyo, . (Buletin Nutrisi dan Makanan Ternak, 2013)
The aim of this experiment was to examine the rumen microbial degradation of feedstuffs for ruminant in a consecutive batch culture system (CBC). The feedstuffs were incubated with mixed rumen microbes in the CBC system according to the methods of Ismartoyo dkk (1994), Ismartoyo and Budiman (2000). The results of this experiment indicated that there was variation in the dry matter (DM) loss between feed samples ranging from 31% for markisa seed to 48.2% for jonga-jonga. Similarly the patterns and the slopes of DM losses during 6 serial of incubation varied between the feed samples. The slopes of the DM losses for cacao pods, jonga-jonga, and markisa seed were â0.62, -0.08, dan â2.34, respectively, indicating that rumen microbes failed to adapt to the presences of these three substrates. Whereas the slopes of kapuk seed and markisa pods were 0.20 and 2.23 suggesting that the rumen microbes appeared to adapt to the presence of these two substrates.